2020
DOI: 10.3390/en13081903
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Identification of the Material Composition of PV Modules with Mobile Spectroscopic Devices

Abstract: With the increased development of portable and handheld molecular spectrometers within recent years, new fields of applications have opened up, such as their use (i) for material identification of samples contained in large and non-portable components and (ii) the detection of material degradation effects and failures directly in the plant. The usability and transferability of well-established analytical characterization techniques, such as attenuated total reflection (ATR) Infrared (IR)-, Raman, and Near-Infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Some of these methods do not require specific sampling (e.g., determination of the indentation module, medium, and near infrared spectroscopies). In contrast, other methods require microsamples (e.g., determination of the modulus of elasticity profile, IR spectroscopy for laboratory testing, thermogravimetry analysis, density measurements, gel fraction determination, and solvent absorption) [14][15][16][17][18][19]. Many evaluations are based on the measurement of physicochemical properties (such as infrared spectra, melting/crystallization temperature [20], glass transition temperature or mechanical tests [21], mass loss during laboratory aging [22], or electrical tests) rather than on oxidation induction time (OIT) tests.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these methods do not require specific sampling (e.g., determination of the indentation module, medium, and near infrared spectroscopies). In contrast, other methods require microsamples (e.g., determination of the modulus of elasticity profile, IR spectroscopy for laboratory testing, thermogravimetry analysis, density measurements, gel fraction determination, and solvent absorption) [14][15][16][17][18][19]. Many evaluations are based on the measurement of physicochemical properties (such as infrared spectra, melting/crystallization temperature [20], glass transition temperature or mechanical tests [21], mass loss during laboratory aging [22], or electrical tests) rather than on oxidation induction time (OIT) tests.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic methods, such as Fourier‐transform infrared (FTIR), Raman and fluorescence spectroscopy, were found to be most suitable to address this challenge due to their high chemical specificity and non‐destructive character 1,7,10–14 . However, these techniques are capable of probing only the BS surface layer and cannot provide information on the inner structure of multi‐layer BSs that are typically several hundred μm thick.…”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques are capable of probing only the BS surface layer and cannot provide information on the inner structure of multi‐layer BSs that are typically several hundred μm thick. By this reason, the investigations into structure and degradation state of multi‐layer BSs using Raman, FTIR and fluorescence spectroscopy typically have an invasive character and need to be performed on BS cross‐sections 7,13–17 . In‐depth non‐invasive probing by confocal Raman spectroscopy is feasible for new PV modules but typically hindered for field‐aged samples due to a strong fluorescence from partially degraded encapsulant and BS materials 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is to identify the polymers present in the layer structure with spectroscopic methods. To this end, Eder et al have shown the possibility to identify the layer stacks on-site with spectroscopic methods (Raman and NIR) [6]. However, on-site analysis of the material is typically limited to known layer stacks, that can be classified and might be not suitable to identify.…”
Section: Introductionmentioning
confidence: 99%